2011
DOI: 10.4236/jcdsa.2011.13009
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Aged Skin with a pH 4 Skin Care Product Normalizes Increased Skin Surface pH and Improves Barrier Function: Results of a Pilot Study

Abstract: The physiological skin surface pH is just below 5. With age the skin surface pH increases up to 6. An increased pH correlates with reduced barrier integrity/cohesion. The present pilot study assesses possible normalization of an increased skin surface pH of the elderly and improvement of barrier function via application of ≈pH 4.0 skin care products. Baseline skin surface pH was determined in elderly (80+ years old; n = 15) compared to middle aged adults (31 - 50 years old; n = 15). The effect of o/w emulsions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 37 publications
3
30
0
2
Order By: Relevance
“…However, application in this study was only for a short-term period of 7 days. Interestingly, comparable effects were observed with a pH 4 O/W emulsion after 14 days of application [21]. However, in this study no further decrease after 14 days was observed.…”
Section: Discussionmentioning
confidence: 41%
“…However, application in this study was only for a short-term period of 7 days. Interestingly, comparable effects were observed with a pH 4 O/W emulsion after 14 days of application [21]. However, in this study no further decrease after 14 days was observed.…”
Section: Discussionmentioning
confidence: 41%
“…More research addressing this topic may help affected patients and promote changes in skin hygiene and skin care behavior. For the elderly, who are also known to have elevated pH ss values and often suffer from dry skin, acidic toiletries have already been recommended in the past [15,19,21,22,33]. …”
Section: Discussionmentioning
confidence: 99%
“…These findings have led to the development of acidic skin care products. Several target groups that may profit from these products in particular have been defined in other studies (e.g., elderly, patients with atopic dermatitis, diabetics) [14,15,19,20,21,22]. Prior research of our study group examined the effect of a pH 4 water-in-oil (W/O) emulsion as well as a 10% α-hydroxy acid O/W emulsion on pH ss and pH sc in healthy subjects and diabetics [19,23].…”
Section: Introductionmentioning
confidence: 99%
“…An increased pH correlates with reduced barrier, integrity/cohesion. In a study it was postulated that long-term acidic skin care (pH 3.5 to pH 4.0) normalizes the increased skin pH of the elderly, improves the integrity of the epidermal barrier and therefore reduces skin problems in these individuals 27 . The pH of our prepared AV blended COL-CS gel was found to be 4.5, which indicates that our prepared gel is perfect to be used as a long term skin care product.…”
Section: Fig 2: Sa-β-gal Positive Nih3t3 Mouse Fibro Blasts Cells (Cmentioning
confidence: 99%